Allograft Reconstruction for the Treatment of Musculoskeletal Tumors of the Upper Extremity. (14th February 2013) - Aponte-Tinao, Luis A.; Ayerza, Miguel A.; Muscolo, D. Luis; Farfalli, German L.
Abstract : In comparison with the lower extremity, there is relatively paucity literature reporting survival and clinical results of allograft reconstructions after excision of a bone tumor of the upper extremity. We analyze the survival of allograft reconstructions in the upper extremity and analyze the final functional score according to anatomical site and type of reconstruction. A consecutive series of 70 allograft reconstruction in the upper limb with a mean followup of 5 years was analyzed, 38 osteoarticular allografts, 24 allograft-prosthetic composites, and 8 intercalary allografts. Kaplan-Meier survival analysis of the allografts was performed, with implant revision for any cause and amputation used as the end points. The function evaluation was performed using MSTS functional score. Sixteen patients (23%) had revision surgery for 5 factures, 2 infections, 5 allograft resorptions, and 2 local recurrences. Allograft survival at five years was 79% and 69% at ten years. In the group of patients treated with an osteoarticular allograft the articular surface survival was 90% at five years and 54% at ten years. The limb salvage rate was 98% at five and 10 years. We conclude that articular deterioration and fracture were the most frequent mode of failure in proximal humeral osteoarticular reconstructions and allograft resorption in elbow reconstructions. The best functional score was observed in the intercalary humeral allograft.